Trajetória escolar: desafios e possibilidades da Socioeducação na cidade do Recife (PE) - Pessoa, Vanessa Karla Souza (Universidade Federal de São Carlos, 2014)
The present study, developed in the line of research for Social Practices and Educational Processes, second major theme, investigated the facts that are related to the schooling process, from the reality of teenagers whose had fulfillment of educative-partner measures in open environment in the municipality of Recife, and who were being monitored through the Specialized Social Assistance Reference Center (Centro de Referência Especializado de Assistência Social – CREAS) and their school itself. The adolescents in this research are male, have the age bracket of fifteen (15) to eighteen (18) uncompleted years and were in socio- educational monitoring by the team of one out of six (06) city CREAS, presenting abandonment and educational failure history records. Besides them, professionals of CREAS and the academic environment were heard. The adolescents arrive to the educational services stigmatized as marginals, bandits and dangerous. It is up to the socio-educative politics, social assistance and education to recognize them as worthy subjects, with access to basic social services, in a way to compensate for all their insufficient trajectory or total absence of the state’s protective measures when it comes to access to school and minimal necessary social conditions to survive. Focus groups were performed with the participant adolescents and semi structured interviews with their relatives and professionals from CREAS, alongside professionals from the schools were made. It was adopted the materialist, historical and dialectical perspective as theoretical fundament to the defense of a social education, human-emancipation-oriented and ethical assumptions in an emancipating education. The results of this research point three (03) analyzing categories: survival need and life project; racism and prejudice; educational failure and the synthesis category: the research as social practicing: the insurgency of educational processes. The categories dialogue about the struggles that surface in the context of social exclusion, in which the participating adolescents are submerged regarding the full access of educational rights. The social context presented brings violent scaring, miserability, discrimination and prejudice, characterized by a society which gives preference to macroeconomic politics and still need to better develop educational processes in social practices from public services by the community which promote socio-education and can relate to human resources alongside values, attitude, positions and posture changes in their lives. Reflecting, like so, the need of emancipating public politics in a socially transforming perspective.
School Trajectory: challenges and possibilities for socio-education in the city of Recife (PE)
Keywords: Socioeducação; Centro de Referência Especializado da Assistência Social; Intersetorialidade; Educação; Práticas sociais e processos educativos; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO